Prevalence, demographics, and complications of cleft palate surgery. Issue 6 (June 2015) - Mahboubi, Hossein; Truong, Adam; Pham, Nguyen S.
Abstract: Introduction: Current published data on the demographics of cleft lip and palate is sparse and differs intranationally in reported incidence, demographics, and complication rates, making accurate local data both valuable and useful. We investigate the prevalence, demographics, and complications of cleft palate correction surgery in the inpatient setting over a 15-year period. Methods: A retrospective review of The California Hospital Discharge Data sets of all pediatric patients who underwent cleft palate repair or cleft palate revision from 1997 to 2011. Children's hospitals (CHs) were analyzed as a separate group. For each record, age, gender, ethnicity, length of stay, total charges, principal payer, complications, and disposition were analyzed. Results: 10, 450 correction surgeries were performed during 1997–2011. This was an annual case-volume of 697 and annual population-adjusted rate of 2.0, neither of which changed over time ( p = 0.9 and 0.06, respectively). Of all surgeries, 21.5% were revisions, 48.3% were performed in CHs, 56.2% were performed on males, and 65.5% were performed on Caucasians. The median length of stay was 1 day, which did not change over time ( p = 1.0). The median total charges increased from 9.074 to 35, 643 over the studied period ( p < 0.001). Admission to CHs was associated with shorter stay (1–3 days vs. 1–4 days) and higher total charges (15, 560 vs. 13, 242; both p < 0.001). Complications occurred in 393 (3.8%) of the surgeries. This percentage did not change over time ( p = 0.2). The most common complication was fistula/abscess/infection, which occurred in 159 cases (1.5%). Respiratory complications requiring ventilation occurred 66 cases (0.6%). Complications were more common in CHs (4.8% vs. 2.8%; p < 0.001). Mortality rate was <0.1%. Conclusions: Our study constitutes the entire surgical cohort within a state, allowing for an accurate representation of the true perioperative complication rate of these procedures. The prevalence, demographics, and outcomes of the cleft palate correction surgery have remained unchanged during 1997–2011. Collectively, our data suggest that primary and secondary palatoplasty present low perioperative risk.